1981
DOI: 10.1901/jaba.1981.14-3
|View full text |Cite
|
Sign up to set email alerts
|

Normal Peer Models and Autistic Children's Learning

Abstract: Present research and legislation regarding mainstreaming autistic children into normal classrooms have raised the importance of studying whether autistic children can benefit from observing normal peer models. The present investigation systematically assessed whether autistic children's learning of discrimination tasks could be improved if they observed normal children perform the tasks correctly. In the context of a multiple baseline design, four autistic children worked on five discrimination tasks that thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
67
0
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 43 publications
3
67
0
1
Order By: Relevance
“…Specifically, a time delay procedure (Charlop et al, 1985;Halle, Marshall, & Spradlin, 1979) (Charlop, Schreibman, & Tryon, 1983;Egel, Richman, & Koegel, 1981) were used in an attempt to teach the children to spontaneously vocalize "I like you" or "I love you" in response to a hug by a familiar person or their mother, respectively. We employed the definition of spontaneity used in Charlop et al (1985): "a verbal response to a nonverbal discriminative stimulus in the absence of a verbal discriminative stimulus."…”
Section: Increasing Autistic Children's Spontaneous Verbalizations Ofmentioning
confidence: 99%
“…Specifically, a time delay procedure (Charlop et al, 1985;Halle, Marshall, & Spradlin, 1979) (Charlop, Schreibman, & Tryon, 1983;Egel, Richman, & Koegel, 1981) were used in an attempt to teach the children to spontaneously vocalize "I like you" or "I love you" in response to a hug by a familiar person or their mother, respectively. We employed the definition of spontaneity used in Charlop et al (1985): "a verbal response to a nonverbal discriminative stimulus in the absence of a verbal discriminative stimulus."…”
Section: Increasing Autistic Children's Spontaneous Verbalizations Ofmentioning
confidence: 99%
“…This finding was replicated by Werts, Caldwell, and Wolery (1996), who found that students with disabilities who could not perform a task showed higher accuracy after observing a typically developing peer emit the chains accurately. Children with autism demonstrated color discriminations after observing typically developing students perform color discrimination tasks (Egel, Richman, & Koegel, 1981). Rehfeldt, Latimore, and Stromer (2003) found that after children and adults with developmental disabilities observed a person without disabilities model prerequisite conditional discriminations, several of the participants demonstrated full stimulus class formation for reading skills.…”
mentioning
confidence: 99%
“…A strong case has been made for peerinvolved procedures such as modeling, prompting, and cross-age tutoring (e.g., Charlop, Schreibman, & Tryon, 1983;Egel, Richman, & Koegel, 1981;Kamps, Locke, Delquadri, & Hall, 1989). In addition, various investigations have demonstrated peer strategies to be an appropriate vehicle for improving social skills and development.…”
mentioning
confidence: 99%
“…Other restrictions or limiting characteristics of academic and social investigations have included (a) the use of peers that are much older than the students with disabilities, (b) the use of "reverse mainstreaming" (i.e., bringing the general education peers to the special education classrooms or isolated environments), or (c) significant modifications of the general education program or costly, intensive training for the students with disabilities (e.g., Almond, Rodgers, & Krug, 1979;Carr & Darcy, 1990;Egel et al, 1981;Haring, Breen, Pitts-Conway, Lee, & Gaylord-Ross, 1987;. Therefore, additional research is needed to determine the effects of peer-mediated strategies on academic and social skills of children with autism in integrated classroom settings.…”
mentioning
confidence: 99%